Oxidative stress in the interruption of mechanical ventilation in patients with traumatic brain injury: a randomized, blind study - Moraes, Anderson Antunes da Costa; Araujo, Luã Alves; Araújo, Rodrigo Alcântara Carnevalli de; Rocha, Rodrigo Santiago Barbosa; Costa, Leonardo Ramos Nicolau da; Gonçalves, Kéven Lorena de Paula; Lima, Gabriela Martins de (ABCS Health Sciences, 2018)
Introduction: The toxic effects of oxygen are not well established in human. Objective: To analyze the oxidative stress levels (EOx) in the interruption of mechanical ventilation (MV) in PSV and T-tube in patients with TBI. Methods: prospective, longitudinal, analytical, randomized and blind study. Twelve patients were assigned to PSV (n=6); T-tube (n=6) groups. The MV interruption occurred in: PSV- (Δ 7 cmH2O) and PEEP (5 cmH2O). T-tube - the patient was connected to the T-tube with 0.4 FiO2 for 30 minutes. Morphological evaluation of EOx in the blood plasma was performed by the Dry layer oxidative test. The collection was performed: with 24h of MV, before the test, in 15 ‘of test and after the PSV or T-tube. For the analysis of normality, the Shapiro-Wilk test was used; for intragroup analysis and intergroups, the ANOVA test followed by Tukey; for correlation the Spearman correlation - p value 5%. Results: There was no statistically significant increase in the extracellular matrix discontinuity in the groups (p> 0.05). EOx levels were elevated (grade IIImoderate) in the first evaluations. No significant correlation was found between the VM parameters and the EOx. The PSV group remained on average 12.33 days under MV, with EOx of 29.02 (grade III/moderate) - r=0.8, p=0.01; the T-tube group averaged 12.83±2.2 days, with EOx of 31.03±5.41 (grade IV/severe) - r=0.9, p=0.07. Conclusion: there was no difference in the EOx behavior between the methods of MV interruption. However, the EOx increased with the VM time.